Diseño de un sistema de indicadores para la sostenibilidad de las actividades del turismo rural en Manabí - Bravo Rodríguez, Evelyn Fernanda (2022)
The objective of this research was to design a system of indicators for the sustainability of rural tourism activities in Manabí, for which the following procedures were carried out: The current situation of rural tourism in Manabí was diagnosed, through the characterization and evaluation rural tourism management in the province. Next, the factors that intervene in the sustainability of rural tourism were identified through bibliographic review, interviews with GAD authorities and surveys of representatives of rural tourism enterprises in the cantons under study. Finally, the indicators for the sustainability of rural tourism activities were determined by selecting three indicator systems that were approved through expert criteria. As a first result, it was obtained that the province has eleven cantons with rural tourism enterprises, in which tourism management is deficient, directly affecting rural tourism development. The second result indicates that the main interest of rural communities is the promotion and sustainable development of tourism in their localities; however, other residents claim to have the socio-economic development of their sectors as a priority. As a final result, the system of indicators for the sustainability of rural tourism activities in Manabí was developed. With which it is concluded that the purpose of this system is to evaluate the performance of the activities that take place in the tourism sector in rural areas of the province.